2015
DOI: 10.4236/mme.2015.53005
|View full text |Cite
|
Sign up to set email alerts
|

Whirl Interaction of a Drill Bit with the Bore-Hole Bottom

Abstract: This paper deals with the theoretic simulation of a drill bit whirling under conditions of its contact interaction with the bore-hole bottom rock plane. The bit is considered to be an absolutely rigid ellipsoidal body with uneven surface. It is attached to the lower end of a rotating elastic drill string. In the perturbed state, the bit can roll without sliding on the bore-hole bottom, performing whirling vibrations (the model of dynamic equilibrium with pure rolling when maximum cohesive force does not exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Later, a lot of refinements were introduced in theoretical models of the buckling effects [7][8][9][10][11][12]. Analysis of whirl interaction of a drill bit with the bore-hole bottom was performed by Musa et al [13].…”
Section: Critical Buckling Of Drill Strings In Cylindrical Cavities Omentioning
confidence: 99%
“…Later, a lot of refinements were introduced in theoretical models of the buckling effects [7][8][9][10][11][12]. Analysis of whirl interaction of a drill bit with the bore-hole bottom was performed by Musa et al [13].…”
Section: Critical Buckling Of Drill Strings In Cylindrical Cavities Omentioning
confidence: 99%
“…The paper discussed the analogy between the phenomena of nonholonomic motions of the Celtic stones and the ellipsoidal bits. Also techniques of solution of the equations of the bit whirling were proposed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Such elaborated software permits one to construct its trajectory securing the smallest values of resistance forces and to choose the least energy-consuming and safe regimes of drilling [6]. Nabil W. Musa, et al (2015) discussed the problem of simulation of a drill bit whirling under conditions of its contact interaction with the bore-hole bottom rock plane. It was showed that the problem on rolling of a rigid ellipsoidal drill bit on a bore-hole bottom plane, the bit is supposed to be attached to the lower end of an elastic rotating drill string.…”
Section: Introductionmentioning
confidence: 99%